Effect of health education on knowledge and prevention of hepatitis infection among secondary school students in Ibadan North Local Government Area of Oyo State (2015)
The study examined the effect of health education on knowledge and prevention of hepatitis infection among senior secondary school students in Ibadan North Local Government Area of Oyo State. The research design was pre-test, post test, control group, quasi-experimental design. A total of 180 students were selected from SS1 and SS2 through Multistage sampling techniques. A self-structured questionnaire and instructional guide on health education and hepatitis B were constructed and used for the research. Five research hypotheses were formulated and tested. Data were analyzed using Descriptive statistics and Analysis of Covariance (ANCOVA) at 0.05 level of significance. Finding showed that there was a significant difference in the pre test and post test score of secondary school students following health education intervention, on the knowledge of hepatitis B (F(2,177) = 12.708, P <.05, η(2)=.067).), causes of Hepatitis B (F(2,177) = 7.191, P <.05, η(2) =.039), mode of transmission of Hepatitis B (F(2,177) = 78.683, P <.05, η(2) =.308)., signs and symptoms of hepatitis B (F(2,177) = 35.294, P <.05, η(2) =.166), prevention of hepatitis B(F(2,177) = 17.117, P <.05, η(2) =.088), following a four weeks health education programme in Ibadan North Local Government Area of Oyo State. Based on these findings, the study recommended that health education/ health campaign should be directed to school students and Specific risk practices such as unsafe sexual intercourse, multiple sexual partners, sharing of sharp instruments for body piercing and unhealthy medical instrumentations should be discouraged. Governments should make screening free and there should be an adequate management plan for those who tested positive and vaccination of those who tested negative. Existing childhood immunization programs should be intensified to improve coverage.